1991
DOI: 10.1002/casp.2450010109
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping in mothers caring for a child with severe learning difficulties: A test of Lazarus' transactional model of coping

Abstract: The literature on psychological stress among women consistently points to the adverse effects of child rearing on mothers, particularly those caring for children with physical or mental handicaps. Early studies of the effects on family functioning of caring for a child with severe learning difficulties adopted a pathological approach in which it was assumed that psychological distress was inevitable among family members, particularly mothers. Recent research has emphasised that many families cope with and adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 16 publications
(5 reference statements)
7
89
2
Order By: Relevance
“…Also in concordance with this finding Schofield, Bloch, Herrman, Murphy, Nankervis and Singh (1998) submitted that financial difficulties were associated with poorer well-being in the caregivers (as cited by Savage & Baile, 2004). Quine and Pahl (1991) in consistent with these findings affirmed that being middle class with few financial worries appeared to protect the result of stressful behaviour for mothers of children with severe learning difficulties. A plausible explanation to caregivers' low psycho-social well-being may be that caregivers who believe there is little or nothing they can do as a result of their low level of education have little motivation to engage in what is typically viewed as health-engendering behaviours such as regular physician visits.…”
Section: Discussionsupporting
confidence: 85%
“…Also in concordance with this finding Schofield, Bloch, Herrman, Murphy, Nankervis and Singh (1998) submitted that financial difficulties were associated with poorer well-being in the caregivers (as cited by Savage & Baile, 2004). Quine and Pahl (1991) in consistent with these findings affirmed that being middle class with few financial worries appeared to protect the result of stressful behaviour for mothers of children with severe learning difficulties. A plausible explanation to caregivers' low psycho-social well-being may be that caregivers who believe there is little or nothing they can do as a result of their low level of education have little motivation to engage in what is typically viewed as health-engendering behaviours such as regular physician visits.…”
Section: Discussionsupporting
confidence: 85%
“…The theoretical cognitive model of stress and coping (Lazarus and Folkman, 1984) has been used to explain this interaction (Beresford, 1994a;Quine and Pahl, 1991). Within this model, personal coping resources include physical and mental health, personality, beliefs and adaptability, interpersonal, problem-solving and parenting skills, whereas socio-ecological resources include informal (partner, relatives, community) and formal networks which can offer practical, emotional, material and financial support.…”
Section: Introductionmentioning
confidence: 99%
“…Other personal coping resources that mediate stress include maternal health (Sharpley et al, 1997), adjustment to the disability (Quine and Pahl, 1991), positive frames of reference (Harris and McHale, 1989) and religious beliefs (Rogers-Dulan, 1998). Socio-ecological resources which help include partner support (Gowen et al, 1989), quality of family relationships (Dyson, 1993), extended family support (Sharpley et al, 1997), peer support (Stallard and Lenton, 1992) and socio-economic status (Quine and Pahl, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, educational level of mother has an impact on determination of strategies developed by children when they encounter a problem and on their behaviors. Furthermore, it has been determined that problem-solving skills of highly educated parents are better than other parents and these parents can better identify adaptation strategies (Quine & Pahl, 1991). Haveman, Gottlieb, and Heller (1997) reported that mothers with lower educational level spend less time for themselves and experience more intense care responsibilities for their children.…”
Section: Hopelessness Levels In Children With and Without Hearing Impmentioning
confidence: 99%